MAIZE GROWTH RESPONSE TO VARIOUS TYPES AND DOSAGES OF ORGANIC MULCH IN THE DRYLANDS OF SOUTHEAST ACEH - Rada Mayang Sari; Murni Sari Rahayu; Yayuk Purwaningrum (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Drylands face physical and chemical constraints that often limit maize growth. The use of organic mulch is a potential strategy to improve growing conditions and nutrient availability. This study aims to examine the growth response of maize to the application of various types and dosages of organic mulch in dryland. The research utilized a factorial Randomized Block Design (RBD) with two factors: mulch type (Chromolaena odorata, bamboo leaves, and rice husk) and mulch dosage (0, 15, 20, and 25 tons/ha). Parameters observed included plant height at 60 days after planting (DAP) and total plant fresh weight at harvest. The results indicated no significant interaction between mulch type and dosage for all parameters. However, mulch dosage had a highly significant effect on plant height, while both mulch type and dosage independently had a significant effect on plant fresh weight. The application of mulch at a dosage of 15 tons/ha was the effective minimum threshold for significantly increasing growth compared to the control. Bamboo leaf mulch provided the best response to biomass accumulation, achieving the highest average fresh weight (232.08 g). Increasing the dosage beyond 15 tons/ha showed a trend of non-proportional returns (diminishing returns). Consequently, the use of bamboo leaf mulch at a dosage of 15 tons/ha can be recommended to efficiently enhance maize productivity in dryland.